STRUCTURAL HISTORY OF THE METAMORPHIC SOLE OF THE BAY-OF-ISLANDS COMPLEX, WESTERN NEWFOUNDLAND - FERGUSSON, C L; Cawood, Peter Anthony (1995)
Displacement of the Early Ordovician ophiolitic Bay of Islands Complex was accompanied by the development of a metamorphic sole in underlying accreted gabbro, mafic pillow lava, pelite, and psammite. The metamorphic sole contains up to 130 m of amphibolite, underlain by up to 80 m of mafic and pelitic-psammitic schist, which, in turn, overlies chlorite-bearing rocks that overlie mudstone-matrix melange. A major foliation, locally mylonitic and (or) isoclinally folded, is pervasively developed in the greenschists and amphibolites. An extension lineation is widely developed and plunges north in amphibolite and trends east-west in greenschist, consistent with a changing direction of thrust transport from northerly to westerly as the mantle wedge cooled over time. Shear sense criteria in greenschist facies pelitic-psammitic schist indicate thrusting towards the west. In the southwestern Blow-Me-Down massif, two sets of folds postdate development of accretion-related S-L fabrics and resulted in a substantial widening of the metamorphic sole. Late disruption by foliation-parallel, low-angle extensional and steep faults have excised parts of the metamorphic sole, resulting in a marked discontinuity of units along strike. Extensional faults were induced by gravitational spreading as the Coulomb thrust wedge, containing the ophiolite, metamorphic sole, and underlying melange unit, became supercritical. This was probably due to a combination of two factors: (1) development of a substantially weakened basal melange layer and (2) lowering of the basal slope of the wedge as it was thrust over the Ordovician slope onto the shelf.